Od ateizmu do teizmu poprzez krytykę „pięciu dróg” św. Tomasza w świetle myśli Antony’ego Flewa - Mrówka, Angelika (Annales Missiologici Posnanienses, 2020)
Atheism and theism have been seen rather as contradictory points of view, without the possibility to enter into dialogue. In 1966 Antony Flew published a book entitled God and Philosphy, a key work, in which the author criticised theism and later – the logical justification of atheism. He took up a constructive criticism of the Five Ways of St Thomas Aquinas. Flew achieved his goal, because he provoked theists to revise their views and ways of formulating theological arguments. Finally, Antony Flew considered again his own attitude and thanks to conducted debates and discussion with theists, he came to the conclusion that God exists. Antony Flew spent almost his whole life on a quest to find the truth. He could be a positive example of an open-minded philosopher, because only such a person is able to contribute to an open a dialogue between atheism and theism.